PENGARUH SISTEM PETERNAKAN DAN LAMA PENYIMPANAN TERHADAP KUALITAS TELUR ITIK - Swacita, Ida Bagus Ngurah; Cipta, I Putu Sudiantara (Buletin Veteriner Udayana, 2012)
Duck is one of the potential egg poultry production in Indonesia. General farming systemof duck was carried out an intensive and semi-intensive. The effect of difference farmingsystem may be contribute to differences in the duck’s egg quality, especially in relation toaspects of Egg White Index (EWI), Egg Yolk Index (EYI) and Haugh Unit (HU) of duck’segg, as well as to the long storage at room temperature (±28°C). The research usedCompletely Randomized Design (CRD), the pattern of 2 (farming system) x 4 (0,7,14 and21 day) two factor treatments farming system as intensive farming and semi-intensive andfour factor that is a long storage at room temperature. Each treatment combination wasreplicated 4 times. Data were analyzed with ANOVA, and followed by Duncan multiplerange test. Based on these results it can be concluded, farming system intensive and semiintensiveto produce duck’s egg quality with EWI, EYI and HU are not significantlydifferent (P>0.05). EWI, EYI and HU were significantly (P <0.01) influenced by longstorage; if the longer stored, the duck’s egg quality to be decreased.
Keywords: duck egg’s, Egg White Index, Egg Yolk Index, Haugh Unit